Black carbon emissions from trucks and trains in the Midwestern and Northeastern United States from 1977 to 2007. (March 2016) - Brown-Steiner, Benjamin; Hess, Peter; Chen, Jialie; Donaghy, Kieran
Abstract: We have developed a framework to estimate BC emissions from heavy-duty diesel trucks and trains engaged in transporting freight in the Midwestern and Northeastern United States (MNUS) from 1977 to 2007. We first expand on a previous development of a regional econometric input–output model (REIM) that has been used to estimate commodity flows between 13 states in the MNUS (plus the rest of the US) and 13 industrial sectors. These commodity flow data are then distributed over the MNUS using a stylized link-and-node network, which creates great circle transportation links between nodes in each state at the county with the largest population. Freight flows are converted to BC transportation emissions and the resulting BC emissions are compared to the MACCity BC emissions inventory. We find that from 1977 to 2007 potential emission growth from the continued increase in freight tonnage in the MWUS is counteracted by decreases in the BC emission factor of heavy-duty diesel trucks, which results in an overall decrease of BC emissions by 2007. One sector (fabricated metal product manufacturing) has dominated the BC transportation emissions throughout 1977 to 2007 with transportation emissions remaining relatively unchanged from 1977 to 1997 and then decreasing out to 2007. The BC transportation emissions are concentrated in and around the urban centers, which serve as transportation and production nodes for industrial manufacturing. Our BC emissions are distributed along stylized transportation corridors that are not well represented in emissions inventories that largely distribute emissions via a population proxy. The framework established in this study can be used to estimate future BC transportation emissions under a set of stylized economic, technological, and regulatory scenarios. Highlights: BC emissions from trucks and rail have decreased between 1977 and 2007. These decreases are noted despite large growth in the volume of freight shipped. Regulatory efforts to decrease BC emissions from trucks has been largely successful. Historically the fabricated metal industrial sector has dominated BC emissions. However, clustering of transportation results in smaller decreases in urban centers.